A Review on Data Aggregation Protocols in Wireless Networks - Pourgalehdari, O; Salari, M (International Journal of Computer Sciences and Engineering, 2025)
Wireless sensor networks are composed of many cheap sensor nodes with limited sensing, computation, and communication capabilities. These networks have a variety of applications in both military and civilian usage, including battlefield surveillance, target tracking, environmental and health care monitoring, wildfire detection, and traffic regulation. Because of the need to low deployment cost of wireless sensor networks, sensor nodes have simple hardware and this leads severe resource constraints. Bearing in mind the limited resources of sensor nodes, it is critical to minimize the amount of data transmission to improve the average sensor lifetime and the overall bandwidth utilization. The process of summarizing and combining sensor data, which is used to reduce the amount of data transmission in the network, is referred to as data aggregation. Adopting an appropriate data aggregation is significantly important for improving the data accuracy, latency, fault-tolerance, and security. This paper reviews the data aggregation protocols in wireless sensor networks based on the existing research. The study can provide future research directions in this area.